Effects of Inflammation on the Immune Microenvironment in Gastric Cancer - Zhao, Weidan; Liu, Mingqing; Zhang, Mingyue; Wang, Yachen; Zhang, Yingli; Wang, Shiji; Zhang, Nan (Frontiers in Oncology, 2021)
Background: Chronic inflammation and immune cell dysfunction in the tumor microenvironment are key factors in the development and progression of gastric tumors. However, inflammation-related genes associated with gastric cancer prognosis and their relationship with the expression of immune genes are not fully understood. Method: In this study, we established an inflammatory response model score called “Riskscore,” based on differentially expressed genes in gastric cancer. We used Survival and Survminer packages in R to analyze patient survival and prognosis in risk groups. The survival curve was plotted using the Kaplan–Meier method, and the log-rank test was used to assess statistical significance, and we performed the ROC analysis using the R language package to analyze the 1-, 3-, and 5-year survival of patients in the GEO and TCGA databases. Single-factor and multi-factor prognostic analyses were carried out for age, sex, T, N, M, and risk score. Pathway enrichment analysis indicated immune factor-related pathway enrichment in both patient groups. Next, we screened for important genes that are involved in immune cell regulation. Finally, we created a correlation curve to explore the correlation between Riskscore and the expression of these genes. Results: The prognosis was significantly different between high- and low-risk groups, and the survival rate and survival time of the high-risk group were lower than those of the low-risk group. we found that the pathways related to apoptosis, hypoxia, and immunity were most enriched in the risk groups. we found two common tumor-infiltrating immune cell types (i.e., follicular helper T cells and resting dendritic cells) between the two risk groups and identified 10 genes that regulate these cells. Additionally, we found that these 10 genes are positively associated with the two risk groups. Conclusion: Finally, a risk model of the inflammatory response in gastric cancer was established, and the inflammation-related genes used to construct the model were found to be directly related to immune infiltration. This model can be a useful tool in predicting gastric cancer prognosis. Our findings contribute to the development of immunotherapy for the treatment of gastric cancer patients.